A causal model of family socio-demographic factors on parents’ involvement in the provision of basic education and students’ achievement in english language (2012)
Provision of basic education is currently receiving a global attention and a boost in all nations of the world. Research evidence in Nigeria indicates a nation-wide concern over the consistent students’ poor performance in English language particularly in externally conducted examinations. The failure rate in the subject is on the increase in spite of concerted effort to find pedagogical solution within the school system. There is a need for serious government, school and parent collaboration in the provision of basic education to improve students’ achievement. This study, therefore, sought to establish a causal explanation of family socio-demographic factors that influence parental involvement and students’ achievement in English language in Ogun state. The study is an ex-post-facto type which used a multi-stage sampling procedure to select 1,373 students from thirty schools spread across six local government areas in Ogun state. Two instruments were used to collect data. They were Students Achievement Test in English (KR20=0.71) and Questionnaire on Parents’ Involvement (α =0.96). Four research questions were answered in the study. The data obtained were subjected to path analysis. The most meaningful causal model on parents’ involvement had twenty four pathways that were significant at p< 0.05. All the predictor variables (marital status, parents’ education, parents’ occupation, parents’ income, number of children, family size, gender of the child, parental educational expectation) made a total contribution of 7.2% of the variance in parents’ involvement. In all, the total effect on parents’ involvement was more indirect (51.78%) than direct (48.22%). Parents’ education (β=. 20) had the most potent effect on parents’ involvement; followed by parents’ occupation (β=.06), marital status (β=-.07) and family size (β=-.24). Parents’ income, number of children in the family, gender and parents’ expectation had only indirect effect on parents’ involvement. Also, the most meaningful causal model on students’ achievement had twenty five pathways that were significant at p< 0.05. All the predictor variables made a total contribution of 5.2% of the variance in achievement in English language. In all, the total effect on achievement was more indirect (50.13%) than direct (49.87%). Number of children (β=.23) had the most potent effect on achievement in English language, followed by parents’ educational expectation (β=.16), parents’ education (β=.09), parents’ income (β=.05) and family size (β=-.24). Marital structure, parents’ occupation, gender and involvement had only indirect effect on achievement in English language. Parents’ education, family size, parents’ occupation, and marital status directly influenced parents’ involvement; and number of children, parents’ educational expectation, parents’ education, parents’ income and family size directly influenced achievement. Educational administrators, principals, teachers, students and parents should see these variables as very important in improving parental involvement and achievement in English language at the junior secondary school level. Parents’ involvement should be seen as a continuous process to enhance students’ achievement in school.